Financial inclusion in the digital economy. (ADB briefs., 2017)
Digital technology is rapidly becoming the biggest driver around the world of economic innovation, competition, and growth. Even though many people have been excluded from the digital economy, tremendous opportunities are available for it to support financial inclusion for sustainable economic development.